Proceso Contable y Tributario del Comercial Electro Accesorios LOZADA - Olvera Sánchez, Jenniffer Dayana (2018)
Over time, in several civilizations began to exist the need to find a way to have a technique where records can be recorded by the different activities that were carried out either through trade, industry, their provision of services and finances. Accounting is useful in the development of different companies, whether they are small, medium or large, since this tool helps assess and analyze the economic results obtained daily from said organization or company. Electro Accesorios "LOZADA" is a business that started its activities on January 9 of the year 2001, its activity is the sale of accessories for vehicles, the same that was created to meet the needs of the inhabitants of where it is located. This business symbolizes the place where the present case study was executed with the subject: Accounting and Tax Process of the Commercial Electro Accessories "Lozada." Through a small interview conducted with the owner of the business, it was found that the procedure performed on a daily basis does not perform them properly, which is considered very important to account for the different activities that must be properly recorded for the correct control in your business. The purpose of this study is to present a complete, effective and efficient idea that contributes the due knowledge in a positive manner to the business owner, and thus she is in the faculty of ordering, classifying and registering the accounting information of the business. obtain as a final result, information that is useful for decision making.